2020
DOI: 10.21203/rs.3.rs-19269/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Next-Generation Sequencing Analysis of Endometrial Screening Liquid-Based Cytology Specimens A Comparative Study to Tissue Specimens

Abstract: Background: Liquid-based cytology (LBC) is now a widely used method for cytologic screening and cancer diagnosis. Since the cells are fixed with alcohol-based fixatives, and the specimens are stored in a liquid condition, LBC specimens are suitable for genetic analyses. Methods: Here, we established a small cancer gene panel, including 60 genes and 17 microsatellite markers for next-generation sequencing, and applied to residual LBC specimens obtained by endometrial cancer screening to compare with correspondi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…In this study, we chose a moderate throughput approach, but broader approaches are described in the literature. Some NGS panels provide, in addition to the MSI status and the genomic profile, the determination of the tumour mutation burden (TMB) score, a complementary predictive tumour biomarker of immunotherapy efficacy 36,49 . Notably, The Food and Drug Administration (FDA) recently approved a NGS-based broad companion diagnostic (FoundationOne CDx (F1CDx) from Foundation Medicine) for the simultaneous analysis of MSI status, genomic aberrations and TMB in all solid tumors.…”
mentioning
confidence: 99%
“…In this study, we chose a moderate throughput approach, but broader approaches are described in the literature. Some NGS panels provide, in addition to the MSI status and the genomic profile, the determination of the tumour mutation burden (TMB) score, a complementary predictive tumour biomarker of immunotherapy efficacy 36,49 . Notably, The Food and Drug Administration (FDA) recently approved a NGS-based broad companion diagnostic (FoundationOne CDx (F1CDx) from Foundation Medicine) for the simultaneous analysis of MSI status, genomic aberrations and TMB in all solid tumors.…”
mentioning
confidence: 99%
“…These results are in agreement with similar published studies, which have consistently shown concordance between results of molecular testing on FFPE specimens and on liquid cytology specimens, including supernatant with cytopreservative 3,8 and without cytopreservative 7,8 and resuspended cell pellets derived from centrifuged cytology fluid. [9][10][11] Only base pair substitutions and one small deletion were detected in this study. The NGS assay utilized is not designed to detect large insertions or deletions, copy number variations, or gene rearrangements, potentially limiting its utility in nonsmall-cell carcinoma of the lung, where the latter two in particular are recurring genetic alterations.…”
Section: Discussionmentioning
confidence: 54%
“…The results of the current study lend further support to already published evidence for use of LBC specimens and their routine utilization in molecular diagnostics. Not only have these findings been reproduced across multiple fixative types, they are seen across multiple assay types on differing platforms, including next generation sequencing, 3,[7][8][9] Sanger sequencing, 4,5,14 capillary electrophoresis, 4,5 RT-PCR, 10 and varying genetic alterations, from substitutions and insertions/deletions 3,7,8 to microsatellite instability and tumor mutational burden, 9 loss of heterozygosity 4,5 and copy number variations. 12 Furthermore, the current study adds to the growing data that DNA is stable in LBC media over an extended time, allowing delayed DNA isolation and molecular analysis on an as-needed basis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We profiled the patients for their HPV infection status using a polymerase chain reaction (PCR)-based examination, whereas the genomic alterations were profiled using next-generation sequencing (NGS). 11 The 2 cases of vaginal NEC shared a common molecular profile; both were HPV18-positive with a low tumor mutation burden (TMB), low microsatellite instability (MSI) score, and no TP53 and RB gene mutations. This is the first report of an HPV18-infected primary vaginal NEC analyzed using NGS analysis.…”
Section: Introductionmentioning
confidence: 99%